Association of malignant neoplasms with semen quality in Guangdong province, China: A propensity score matching analysis. (13th August 2021) - Fan, Zhaoyu; Wang, Qiling; Xu, Ruijun; Wang, Yaqi; Liu, Tingting; Li, Yingxin; Duan, Yonggang; Liu, Yuewei; Zhang, Xinzong
Abstract: Background: Previous studies have reported lower semen quality in malignant neoplasm patients before antineoplastic treatments, but the adverse effects of malignant neoplasms on semen quality have rarely been quantitatively evaluated. In addition, due to the lack of a comparable control group and limited types of studied malignant neoplasms, the results remain inconsistent and inconclusive. Objectives: To quantitatively evaluate the potential adverse effects of specific malignant neoplasms on semen quality. Materials and methods: We conducted a cross‐sectional study to investigate 445 malignant neoplasm patients undergoing sperm cryopreservation for fertility preservation in Guangdong province, China during 2016–2019. A propensity score matching method was used to select a comparable control group from 9170 sperm donation volunteers. Each subject was analyzed for semen quality. Multivariate linear regression models were employed to assess the association between malignant neoplasm and semen quality. Results: Using the propensity score matching method, 413 (92.8%) malignant neoplasm patients were successfully matched with 798 sperm donation volunteers. Overall, malignant neoplasms were significantly associated with a 0.3 ml, 17.1 × 10 6 /ml, 67.6 × 10 6, 9.8%, 10.2%, and 6.4% reduction in semen volume, sperm concentration, total sperm number, total motility, progressive motility, and normal forms, respectively. Malignant neoplasm of testis, nasopharynx and digestive organs, Hodgkin lymphoma, non‐Hodgkin lymphoma, and leukemia were significantly associated with a reduction in sperm motility and normal forms, while malignant neoplasm of testis, Hodgkin lymphoma, and leukemia were also significantly associated with reduced sperm concentration and/or total sperm number. The reduction in sperm concentration and total sperm number associated with malignant neoplasms was significantly greater in subjects < 30 years. Discussion and conclusion: We found that malignant neoplasms were significantly associated with a reduction in semen quality, which varied across the type of malignant neoplasms. Our results highlight the needs to examine semen quality for young malignant neoplasm patients, especially those who are expected to conceive.